Bisphosphonates in breast cancer radiotherapy: associations with skeletal complications and treatment outcomes - a retrospective cohort study - Baalbaki, Khanom; Hemdanieh, Maya; Yammine, Jeffrey; Sleem, Bshara; Sawaf, Souad; Lakkis, Rawad; Nassereddine, Mohamad; Bodgi, Larry (Frontiers in Oncology, 2026)
IntroductionBreast cancer is the most diagnosed cancer in women worldwide. Radiotherapy is a cornerstone of treatment for both early-stage ductal carcinoma in situ (DCIS) and metastatic disease, but concerns about side effects remain. Bisphosphonates (BPs), particularly zoledronic acid (ZOL), have shown anti-tumor effects in preclinical models and reduce skeletal complications in patients with bone metastases. This study aimed to evaluate the radiosensitizing potential of BPs and their relationship with skeletal complications in breast cancer patients undergoing radiotherapy.MethodsWe conducted a retrospective cohort study at the American University of Beirut Medical Center, including female patients aged 40–65 years with primary DCIS who received radiotherapy between November 2018 and September 2023. Data on patient demographics, tumor characteristics, treatment modalities, and outcomes were extracted from electronic medical records. Associations between BP use and pathologic fractures, musculoskeletal (MSK) complications, and treatment response were analyzed using logistic regression adjusted for relevant confounders.ResultsAmong 397 patients with breast cancer in our cohort, only 122 (30.7%) received ZOL. BP use was independently associated with increased odds of MSK complications (OR = 4.34; 95% CI: 2.42–7.77; p < 0.001) and pathologic fractures (OR = 2.93; 95% CI: 1.37–6.24; p = 0.005). No significant association was observed between BP use and tumor response, skin complications, fatigue, or other adverse effects.ConclusionThese findings likely reflect baseline skeletal fragility rather than a direct harmful effect of BPs. BPs remain an important indicator of bone vulnerability rather than a therapeutic modifier.